Geologic Carbon Sequestration Understanding Reservoir Behavior - Vishal, V.; Singh, T.N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This exclusive compilation written by eminent experts from more than ten countries, outlines the processes and methods for geologic sequestration in different sinks. It discusses and highlights the details of individual storage types, including recent advances in the science and technology of carbon storage. The topic is of immense interest to geoscientists, reservoir engineers, environmentalists and researchers from the scientific and industrial communities working on the methodologies for carbon dioxide storage. Increasing concentrations of anthropogenic carbon dioxide in the atmosphere are often held responsible for the rising temperature of the globe. Geologic sequestration prevents atmospheric release of the waste greenhouse gases by storing them underground for geologically significant periods of time. The book addresses the need for an understanding of carbon reservoir characteristics and behavior. Other book volumes on carbon capture, utilization and storage (CCUS) attempt to cover the entire process of CCUS, but the topic of geologic sequestration is not discussed in detail. This book focuses on the recent trends and up-to-date information on different storage rock types, ranging from deep saline aquifers to coal to basaltic formations.
1. Carbon capture, transport and geologic storage: A brief introduction -- 2. Algorithms for CO2 storage capacity estimation: Review and Case study -- 3. Trapping mechanism of CO2 storage in deep saline aquifers: brief review -- 4. Monitoring of CO2 plume migration in deep saline formations with kinetic interface sensitive tracers (A numerical modelling study for the laboratory) -- 5. Monitoring of soil gases in the characterization stage of CO2 storage in saline aquifers and possible effects of CO2 leakages in the groundwater system -- 6. CO2 storage capacity estimates for a Norwegian and a Swedish aquifer using different approaches - from theoretical volumes, basin modelling to reservoir models -- 7. Determination of CO2-brine-rock interactions for carbon dioxide sequestration using SEM-EDS methods -- 8. Geological Considerations for CO2 Storage in Coal -- 9. A review summary on multiple aspects of coal seam sequestration -- 10. CO2 Storage in Depleted/Producing Oil reservoirs -- 11. Mineral Carbonation in Ultramafic and Basaltic Rocks -- 12. Ocean Applications for Carbon Dioxide Sequestration -- 13. Risk Assessment of the Geological Storage of CO2: A Review -- 14. Numerical modelling of CO2 gas injection with hydrate formation: A Case Study in the Laboratory-Scale Sand Sediment -- 15. Security Assessment on Geological Storage of CO2: Application to Hontomin Site.
Keywords: Earth sciences; Fossil fuels; Climate change; Geotechnical engineering; Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Fossil Fuels (incl. Carbon Capture).; Climate Change/Climate Change Impacts; Electronic books